The effects of ethnic and social segregation on children and adolescents: Recent research and results from a German multilevel study - Dietrich Oberwittler (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2007)
This paper, in a first part, reviews current literature on the effects of ethnic and social segregation on children and adolescents. In a second part, it reports results of an empirical study on this issue conducted by the author in two German cities. In recent research, the effects of segregation have been framed as possible `contextual effects' of neighbourhoods, i.e. as separate factors beyond the individual effects of social disadvantage. The paper discusses theoretical and methodological underpinnings of recent studies that use nested samples of individuals in different types of neighbourhoods and multilevel analyses. While there is some evidence of detrimental effects of segregation on outcomes like health, education and crime, this mostly comes from the US. In Europe few relevant studies have been conducted and support for these hypotheses is much weaker. – – Dieses Arbeitspapier berichtet über die aktuelle Forschungsliteratur zu den Auswirkungen ethnischer und sozialer Segregation auf Kinder und Jugendliche sowie über die Ergebnisse einer empirischen Studie zu diesem Thema, die der Autor in zwei deutschen Großstädten durchgeführt hat. In der gegenwärtigen Forschung werden die Auswirkungen von Segregation als mögliche Kontexteffekte des Stadtviertels jenseits der individuellen Effekte sozialer Benachteiligung anhand geschachtelter Stichproben von Individuen in unterschiedlichen Stadtvierteln und mit Hilfe der Mehrebenenanalyse untersucht. Die theoretischen und methodischen Grundlagen dieses Ansatzes werden diskutiert. In den Ergebnissen gibt es einzelne empirische Hinweise auf die Existenz nachteiliger Effekte der Segregation in den Bereichen Gesundheit, Bildung und Kriminalität, doch stammen diese überwiegend aus U.S.-amerikanischen Studien, während europäischen Studien in diesem Bereich seltener sind und weniger eindeutige Ergebnisse hervorgebracht haben.
Keywords: 300